Aberrant individual large-scale functional network connectivity and topology in chronic insomnia disorder with and without depression - Chen, Meiling; Shao, Heng; Wang, Libo; Ma, Jianing; Chen, Jin; Li, Junying; Zhong, Jingmei; Zhu, Baosheng; Bi, Bin; Chen, Kexuan; Wang, Jiaojian; Gong, Liang (Progress in neuro-psychopharmacology & biological psychiatry, 2025)
Insomnia is increasingly prevalent with significant associations with depression. Delineating specific neural circuits for chronic insomnia disorder (CID) with and without depressive symptoms is fundamental to develop precision diagnosis and treatment. In this study, we examine static, dynamic and network topology changes of individual large-scale functional network for CID with (CID-D) and without depression to reveal their specific neural underpinnings. Seventeen individual-specific functional brain networks are obtained using a regularized nonnegative matrix factorization technique. Disorders-shared and -specific differences in static and dynamic large-scale functional network connectivities within or between the cognitive control network, dorsal attention network, visual network, limbic network, and default mode network are found for CID and CID-D. Additionally, CID and CID-D groups showed compromised network topological architecture including reduced small-world properties, clustering coefficients and modularity indicating decreased network efficiency and impaired functional segregation. Moreover, the altered neuroimaging indices show significant associations with clinical manifestations and could serve as effective neuromarkers to distinguish among healthy controls, CID and CID-D. Taken together, these findings provide novel insights into the neural basis of CID and CID-D, which may facilitate developing new diagnostic and therapeutic approaches. •The neural basis for chronic insomnia disorder with and without depression was explored.•Individual large-scale functional network mapping was conducted for each subject.•Both static and dynamic large-scale functional network connectivity and network topology were analyzed.•The shared- and specific-neural markers for chronic insomnia disorder with and without depression were established.